PENGARUH POLA ASUH OTORITER TERHADAP PERILAKU BULLYING PESERTA DIDIK (Studi Deskriptif Analisis di SMA Negeri 4 Bandung) - Silvia Aprilia, - (2022)
Bullying behavior is recorded as a case of violence that can cause victims, carried out intentionally by several teenagers. Risk factors associated with behavioral disorders, namely biological, family, environmental and psychosocial factors. Parents who play an important role in the pattern of parenting for children cannot fully fulfill their rights and obligations. Many types of parenting are carried out by parents, one of which is authoritarian parenting which emphasizes punishment. The purpose of this study is to analyze how much influence the authoritarian parenting style has on the bullying behavior of students. By taking a sample of 292 students in SMA Negeri 4 Bandung, using a quantitative approach descriptive method using a questionnaire as a data collection technique. The results of this study H0 is accepted and H1 is rejected indicating that there is no influence between the two variables. The recommendations in this study are expected to be information for all parents in applying parenting to their children.